Observations on the Magisterium’s Gender Anthropology and Its Consequences for Women in the Catholic Church - Bernhard Sven Anuth (Religions, 2022)
The Catholic Church has a gender-hierarchical constitution. The Church’s magisterium justifies this structure and the lack of gender equality within the Church with the complementary sexuality of human beings as man and woman, which is considered to be the will of God. In this article, this doctrine is presented in detail, based on relevant documents of the Church‘s magisterium, and is classified with regard to its consequences for women within the Catholic Church. Even though the Church rejects criticism of its position as a dangerous “(gender) ideology”, fewer and fewer women (and men) accept its teaching of a specific “genius of women” and of the assigned gender-specific roles in the Church and in the world associated with it. Moreover, there is now a growing awareness that violence against women is usually related to such hierarchical gender concepts.